The impact of the COVID-19 pandemic on the small cell lung cancer epidemiology - Xuemei Zhang; Lele Chang; Wansu Xu (Discover Oncology)
Abstract Objectives To explore the potential impact of the coronavirus disease 2019 (COVID-19) pandemic on the epidemiology of small-cell lung cancer (SCLC). Methods SCLC patients were collected from the Surveillance, Epidemiology, and End-Results (SEER) database (diagnosed between 2018 and 2021) and grouped according to the timing of the COVID-19 pandemic. Intergroup comparisons and survival analyses were performed on clinicopathologic characteristics and survival data to explore the differences in morbidity characteristics and survival in SCLC patients before and after the pandemic. Results SCLC Patients diagnosed in the post-COVID-19 pandemic tended to have earlier tumor stage, receive chemotherapy (OR 1.14, 95% CI 1.02–1.27, P-value = 0.02) rather than radiotherapy (OR 0.89, 95% CI 0.84–0.96, P-value < 0.01), and have increased time to treatment delay. Balancing follow-up time and constructing improved survival curves, patients with SCLC diagnosed after the pandemic tended to have a worse prognosis. Conclusions Differences in some clinicopathologic factors and treatment choices, or the pandemic itself, may result in a tendency for patients with SCLC diagnosed after the pandemic to have a worse prognosis, alerting clinicians to the need to focus on the management and treatment of this population.